КОМБИНИРОВАННЫЙ РАСЧЕТ УСИЛЕНИЯ ЭЛЕКТРИЧЕСКОГО ПОЛЯ В ОКРЕСТНОСТИ ВЕРШИН ТОНКИХ ПРОВОДЯЩИХ СТЕРЖНЕЙ - Резинкина, М.М.; Резинкин, О.Л.; Светличная, Е.Е.; Сосина, Е.В. (Інститут електродинаміки НАН України, Київ, 2015)
The two stages method of calculation of applied electric field (EF) stress increase in the vicinity of tops of thin conducting rods, which length (L) bigger than their radius (R) by 100-1000 times, has been described. At first, EF is determined in the area including the whole rod with a spatial step L Δ , depending on L. At this, it is assumed that on the distance L Δ from the rod’s axis, potentials fall off logarithmically. Then with the help of obtained solution, another calculation of EF is performed in the direct closeness to the rod’s top with spatial step R Δ , depending on R. Comparison of EF distribution in the vicinity of the rod’s top, got by such method with the results calculated at application to all investigated area of a mesh with spatial step R Δ has shown correctness of such approach. This method has been used to obtain the dependence of EF maximum levels stress on the cylindrical rods’ tops on the ratio of L and R. References 11, table 1, figures 5.